Formulation and Evaluation of Antifungal Miconazole Nitrate Medicated Soap - RÉDAI, Emőke Margit; PÉTERFI, Orsolya; VLAD, Robert Alexandru; ANTONOAEA, Paula; TODORAN, Nicoleta; CIURBA, Adriana; FÜLÖP, Ibolya Zita; BARABÁS, Enikő; SIPOS, Emese (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Miconazole nitrate containing soaps were formulated using one commercially available soap base and three cold process soap bases with various lipids. The aim of our work was to investigate the antimicrobial activity and physicochemical properties of the obtained formulations. The water loss and hardness of the soaps was determined 1, 2, 4 and 9 weeks after preparation. The pH and foamability were determined after 9 weeks of curing time. Two Gram-positive, four Gram-negative bacteria and two yeast (Candida spp.) strains were used in the microbial study. The miconazole content was determined with HPLC-UV analysis. Antimicrobial assay showed that all medicated soaps were effective against Candida albicans. The API had minimal influence on the physicochemical properties (water loss, pH, foamability and consistency) of the soaps. All soaps possessed good lathering properties and an alkaline pH (9.2-11.3). The miconazole content of the soaps varied from 2.72 % to 5.12 % as revealed by HPLC-UV analysis.